Animal Teeth in a Late Mesolithic Woman’s Grave, Reconstructed as a Rattling Ornament on a Baby Pouch - Riitta Raino; Annemies Tamboer (EXARC Journal)
In one of the Late Mesolithic graves at Skateholm, Sweden, dating from 5500–4800 BC, was buried a woman together with a newborn baby. Altogether 32 perforated wild boar (Sus scrofa) teeth, along with traces of red ochre pigment, were found in this grave. We interpreted these artefacts as a rattling ornament decorating a baby pouch of leather coloured with red ochre. We made an experimental reconstruction and found out that the tooth pendants rattle against one another when the pouch is carried, for example, rocked to and fro. The reconstruction currently is on display in the European Music Archaeology Project’s travelling exhibition on archaeological instruments.